Atrial Flutter in a Giant Anteater (Myrmecophaga tridactyla): Electrocardiographic Diagnosis and Echocardiographic Evaluation - Marangoni, Marina; Rodrigues Marques, Ana Letícia; Mamgue, Vitor Eduardo; Fagundes Meznerovvicz, Ademar Francisco; Takazono Lemes, Mel; Braz, Paulo Henrique; Champion, Tatiana (Acta Scientiae Veterinariae, 2026)
Background: Cardiac evaluations in wild animals are essential for assessing health status prior to rehabilitation and release. The giant anteater (Myrmecophaga tridactyla), classified as vulnerable by the IUCN, frequently requires rescue and health assessments due to increasing threats from habitat destruction. Cardiovascular assessments such as electrocardiography (ECG) and echocardiography (ECHO) are critical but remain scarcely studied in this species. This report aimed to describe the 1st diagnosis of atrial flutter in a free-ranging giant anteater using ECG, supported by an echocardiographic evaluation to investigate possible structural alterations. Case: A free-ranging female giant anteater was rescued in Paraná, Brazil, and chemically restrained with ketamine, midazolam, and morphine. Physical examination showed ectoparasites, superficial lesions, and signs of estrus. The animal weighed 40 kg and had stable physiological parameters. The animal underwent electrocardiogram (ECG) monitoring using an INcardio X® device. ECG findings revealed paroxysmal atrial flutter, characterized by regular atrial activity without distinct P waves. The ECG showed a mean heart rate of 54 bpm, a QRS duration of 64 ms, a QTc of 332 ms, and an ST segment depression of -0.3 mV. Heart rate variability was analyzed using time-domain measures and nonlinear methods, and indicated an SDNN of 68.7 ms, RMSSD of 32.9 ms, CSI of 4.05, and CVI of 1.03. These data suggested transient autonomic alterations likely related to handling stress and sedation. Echocardiogram (ECHO) was performed using the SonoSite M-TURBO® ultrasound system equipped with a sector transducer. ECHO showed no structural cardiac abnormalities. Measurements such as LVIDs (1.47 cm), IVSs (1.46 cm), LVPWs (1.62 cm), and LA/AO ratio (1.06) were within or slightly above reference values, possibly due to the animal's adult age and natural cardiac growth. The ejection fraction was 72%, and fractional shortening was 40.1%, indicating preserved systolic function. Discussion: This was the 1st electrocardiographic record of atrial flutter in a giant anteater. The ECG pattern was consistent with atypical type II flutter, with positive F waves in inferior leads, suggesting a clockwise reentrant circuit, with activation of the interatrial septum occurring from superior to inferior. Although atrial flutter in other species is often linked to structural heart disease or atrial remodeling, ECHO findings in this case ruled out significant cardiac anomalies. Minor deviations from reference ranges were attributed to age-related growth, as the animal was older than individuals in previous studies. The data suggest that atrial flutter was likely stress-induced or related to the sedative protocol. These findings highlight the importance of cardiovascular monitoring during wildlife rescue operations and the potential role of sedative agents in arrhythmogenesis. The transient nature of the arrhythmia and absence of structural abnormalities supported the animal's release. Further research is crucial to refine sedation protocols and better understand the cardiovascular physiology of this vulnerable species. This case emphasizes the value of combining ECG and ECHO for comprehensive cardiac assessment in wildlife and contributes original reference data for future health evaluations of giant anteaters. Keywords: electrocardiography, echocardiography, wildlife conservation, sedative protocols, arrhythmogenesis.